Hyperglycemic condition during puberty increases collagen fibers deposition in the prostatic stroma and reduces MMP-2 activity - Santos, Sérgio Alexandre Alcantara dos [UNESP]; Porto Amorim, Elaine Manoela; Ribeiro, Larissa Mayume [UNESP]; Rinaldi, Jaqueline Carvalho; Delella, Flávia Karina; Justulin, Luis Antonio [UNESP]; Felisbino, Sérgio Luis [UNESP] (Elsevier, 2017)
Puberty is an important period for the growth and maturation of the male reproductive system, and is also a critical window for endocrine or environmental interference. The physiological levels of circulating insulin and hyperglycemic control are important factors for a normal prostate growth. Hyperglycemia during puberty is reported to retard the growth of the prostate gland, with remarkable effects on the epithelial compartment. Here, we investigated the impact of hyperglycemia along with a simultaneous or late insulin replacement on the ventral prostate growth in rats during puberty, paying special attention to the deposition of collagen fibers and activities of gelatinase, matrix metalloproteinase-2 (MMP-2), and −9 (MMP-9). Hyperglycemia was induced by streptozotocin (STZ) administration in 40-day-old male Wistar rats. A subset of hyperglycemic rats underwent an early insulin replacement (three days after the STZ administration), and another subset underwent a late insulin replacement (twenty days after the STZ administration). Animals were euthanized at 60 and/or 80 days of age. The ventral prostatic lobe was processed for picrosirius red staining, type I and III collagen immunohistochemistry, and gelatin zymography. Hyperglycemic animals showed an increased area of collagen fibers in the prostate, which was composed both types of collagens. MMP-2 activity was significantly reduced in the hyperglycemic animals, while MMP-9 activity was very low and showed no alteration. The simultaneous and late insulin administration restored collagen content and MMP-2 activity. In conclusion, puberty is a critical window for prostate maturation and type-1 diabetes-induced hyperglycemia affects the ratio of the prostatic parenchymal and stromal growth, leading to fibrotic tissues by also MMP-2 down regulation.
Keywords: Collagen; Diabetes; Hyperglycemia; Metalloproteinase; Prostate; Puberty